Potential of ground and unground palm oil fuel ash in construction material - Roslee, Faiza; Mohd Kamil, Nor Amani Filzah; Abd Kadir, Aeslina (Penerbit UTHM, 2017)
The uncontrolled bunches of palm oil fuel ash (POFA) leads environmental pollution and hazardous to the human. Besides, POFA can be classified as the high pozzolonic matter. Thes e problem attracts attention tremendous researcher to identify the usage or potential of POFA for overcome the issues. This paper will give a review about the solving problems in a different methods. The researcher found the potential by replaced the cement with POFA as supplemetary. Then the finding shows that POFA can reduce carbon content, loss of ignition and increased mineral oxide composition. Yet, POFA has good pozzolanic material and it can be used in agricultural and construction industries.